Granulometric maps from high resolution satellite images - Mering, Catherine (Image analysis and stereology, 2002)
A new method of land cover mapping from satellite images using granulometric analysis is presented here. Discontinuous landscapes such as steppian bushes of semi arid regions and recently growing urban settlements are especially concerned by this study. Spatial organisations of the land cover are quantified by means of the size distribution analysis of the land cover units extracted from high resolution remotely sensed images. A granulometric map is built by automatic classification of every pixel of the image according to thegranulometric density inside a sliding neighbourhood. Granulometric mappingbrings some advantages over traditional thematic mapping by remote sensing by focusing on fine spatial events and small changes in one peculiar category of the landscape.
Keywords: Delec, velikost; Spacecraft; Particle Size; Slika, obdelava z računalnikom; Urbanizacija; Image Processing, Computer-Assisted; Urbanization; Vesoljska plovila; Paris; Francija; France; Pariz; satelitski posnetki; zemeljsko površje; analiza slik; obdelava slik